2019
DOI: 10.1039/c9ra00705a
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes proliferation and suppresses apoptosis in Ox-LDL stimulated macrophages by regulating the miR-34a/Bcl2 axis

Abstract: Metformin, an antidiabetic drug, has been reported to be involved in atherosclerosis (AS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…A similar upregulation in miR-34a-5p was recorded in the thoracic aortae of ath diet-fed SD rats. Also, the ox-LDL-treated HUVEC and MDMs showed elevated miR-34a-5p expression, in agreement with the reports of other research groups [42][43][44]. Redox-sensitive NF-kb and P53 are transcription factors of intergenic miR-34a-5p.…”
Section: Corm-a1 Alleviates Mir-34a-5p Expression By Altering Its Tra...supporting
confidence: 91%
“…A similar upregulation in miR-34a-5p was recorded in the thoracic aortae of ath diet-fed SD rats. Also, the ox-LDL-treated HUVEC and MDMs showed elevated miR-34a-5p expression, in agreement with the reports of other research groups [42][43][44]. Redox-sensitive NF-kb and P53 are transcription factors of intergenic miR-34a-5p.…”
Section: Corm-a1 Alleviates Mir-34a-5p Expression By Altering Its Tra...supporting
confidence: 91%
“…Metformin treatment increased the immunostaining of BCl2 and decreased immunostaining of active caspase3 and BAX, these finding suggest that metformin could suppress the uterine apoptosis by upregulating BCl2 proteins. It has been shown that metformin suppresses apoptosis by upregulating BCl2 expression in the macrophage cells (Feng et al, 2019). It has been shown that metformin ameliorates uterine defects in the polycystic ovary syndrome rat model (Y. Zhang et al, 2017); on the other hand, it has also been emphasized that metformin might be important to overcome aging and aging‐related diseases (Soukas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%